Yoga for mental health of children: a short review - Davari, Farahnaz; Sadiri, Nahal; Shariat, Arghavan; Soh, Kim Geok (Escola Bahiana de Medicina e Saude Pública, 2016)
This review paper aims to introduce yoga as a method for dealing with stress of children, and discusses how it can help them to balance body and emotion. Children need to listen inward: to their bodies, ideas and their feelings. Yoga helps children on being self aware and taking part in social activities. Method: This review attempted to gather the relevant papers that were previously published on the subject. PubMed, Scopus, and Google Scholar were the sources for findings the articles. Only the articles that were published not later than 2005 were selected. Results: Nowadays, children’s expectations are higher than in the past, and their interest on the internet, media, and other communication technologies has increased. Using these media devices and the time that they spend on it may influence their lifestyles negatively and cause stress. While these technologies are very useful in their life for communication even in learning and entertainment, these sources can also lead to undeveloped attention. This article is suggesting yoga as a helpful method for children to deal with their stress, and to increase their well-being, mental health, and positive feelings. Conclusion: Yoga aids to improve physical and mental health among children and helps students in enhancing resilience, mood and self-regulation skills related to emotion and stress.